Efek Pemberian Infusa Daun Carica papaya Terhadap Perkembangan Vektor Larva Nyamuk Aedes aegypti - VINA LIDYA SETJAPUTRA; STEVEN CHRISTIAN SUSIANTO; RISMA (Universitas Hang Tuah, 2022)
Background: Vector eradication is the most effective strategy to prevent Dengue Hemorrhagic Fever, particularly larvae elimination by larvicide. The papaya leaf (Carica papaya) contains several chemicals used as a larvicidal agent. This study aimed to determine the larvicidal activity of papaya leaf (Carica papaya) infusion against third instar Aedes aegypti larvae as dengue hemorrhagic fever prevention. Method: This was an experimental laboratory study with a post-test-only control group design. We used the third instar of Aedes aegypti mosquito larvae, divided into seven treatment groups, one positive control group, and one negative control group, containing 25 larvae each. The treatment groups were given papaya leaf infusion with concentration of 4%, 4,5%, 5%, 5,5%, 6%, 6,5%, 7%, respectively. The negative control group did not receive any treatment, and the positive control group received Temephos with 1 ppm dose. Larvae mortality was recorded after 24 hours, and we replicated the experiment 3 times. The mortality data were analyzed using a one-way ANOVA test for normally distributed and Kruskal Wallis for not normally distributed. Results: There were no significant differences between treatment groups and negative control group, except in concentration of 6,5% (p=0,034) and 7% (p=0,037) group, and significant differences between all treatment groups compared to the positive control group (p<0,05). Conclusion: Papaya leaf infusion as Aedes aegypti larvicide in concentrations of 6,5% and 7% showed a significant effect on larvae mortality after 24-hour. However, compared to Temephos, it was a less larvicidal effect.